Regulation of intestinal epithelial intercellular adhesion and barrier function by desmosomal cadherin desmocollin-2 - Raya-Sandino, Arturo (Mol Biol Cell, 2021)
The role of desmosomal cadherin desmocollin-2 (Dsc2) in regulating barrier function in intestinal epithelial cells (IECs) is not well understood. Here, we report the consequences of silencing Dsc2 on IEC barrier function in vivo using mice with inducible intestinal–epithelial-specific Dsc2 knockdown (KD) (Dsc2(ERΔIEC)). While the small intestinal gross architecture was maintained, loss of epithelial Dsc2 influenced desmosomal plaque structure, which was smaller in size and had increased intermembrane space between adjacent epithelial cells. Functional analysis revealed that loss of Dsc2 increased intestinal permeability in vivo, supporting a role for Dsc2 in the regulation of intestinal epithelial barrier function. These results were corroborated in model human IECs in which Dsc2 KD resulted in decreased cell–cell adhesion and impaired barrier function. It is noteworthy that Dsc2 KD cells exhibited delayed recruitment of desmoglein-2 (Dsg2) to the plasma membrane after calcium switch-induced intercellular junction reassembly, while E-cadherin accumulation was unaffected. Mechanistically, loss of Dsc2 increased desmoplakin (DP I/II) protein expression and promoted intermediate filament interaction with DP I/II and was associated with enhanced tension on desmosomes as measured by a Dsg2-tension sensor. In conclusion, we provide new insights on Dsc2 regulation of mechanical tension, adhesion, and barrier function in IECs.